CRISIS AND CRISIS MANAGEMENT IN HEALTH INSTITUTIONS (COVIT-19) - CİN, Zine and UZUN , Hasan (SSD Journal, 2021)
Crisis are developments that negatively affect individuals, organizations, groups and societies. Crises, due to their nature, shape the life / service quality of societies and organizations negatively. Health needs and priorities of societies / organizations / individuals change in health-related crisis situations. It is possible to overcome this situation without any loss or with the least loss via effective crisis management. This study aims to engender succinct knowledge about crisis and crisis management in health institutions. Sequel to this narrative, it is imperative to examine what health institutions should and should not do in crises such as epidemic diseases, and thus; Institutional memory has been established. Moreso, as factors such as social, economic, and psychological outputs of Covid-19 has been prioritized on the agenda of the World for nearly a year, crisis and crisis management in health institutions became more useful thereafter. Consequently, this study aims to increase the systematic knowledge of institutions and individuals on crisis and crisis management in health and to measure and see at what stage they are sufficient and not sufficient. Therefore, existent or potential crisis or crises will be more accurately isolated or managed.